Measurement of double-differential muon neutrino charged-current interactions on C8H8 without pions in the final state using the T2K off-axis beam - Barr, G; Dewhurst, D; Dolan, S; Duffy, K; Jacob, A; Lu, X; Shah, R; Vacheret, A; Wark, D; Weber, A; The T2K Collaboration (314 others) (American Physical Society, 2016)
We report the measurement of muon neutrino charged-current interactions on carbon without pions in the final state at the T2K beam energy using 5.734×1020 protons on target. For the first time the measurement is reported as a flux-integrated, double-differential cross section in muon kinematic variables (cosθμ, pμ), without correcting for events where a pion is produced and then absorbed by final state interactions. Two analyses are performed with different selections, background evaluations and cross-section extraction methods to demonstrate the robustness of the results against biases due to model-dependent assumptions. The measurements compare favorably with recent models which include nucleon-nucleon correlations but, given the present precision, the measurement does not distinguish among the available models. The data also agree with Monte Carlo simulations which use effective parameters that are tuned to external data to describe the nuclear effects. The total cross section in the full phase space is σ=(0.417±0.047(syst)±0.005(stat))×10-38 cm2 nucleon-1 and the cross section integrated in the region of phase space with largest efficiency and best signal-over-background ratio (cosθμ>0.6 and pμ>200 MeV) is σ=(0.202±0.036(syst)±0.003(stat))×10-38 cm2 nucleon-1.